2019
DOI: 10.1016/j.parkreldis.2019.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Mind the gaps: What we don't know about cognitive impairment in essential tremor

Abstract: Introduction: Although the hallmark feature of essential tremor (ET) is tremor, there is growing appreciation that cognitive impairment also occurs, including increased prevalence of mild cognitive impairment (MCI) and increased prevalence and incidence of dementia. With emerging knowledge of ET-cognitive impairment, come fundamental questions regarding its course, bases, predictors and clinical outcomes. Studies in the general population and in Parkinson's disease (PD), a related movement disorder, offer a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 222 publications
(170 reference statements)
3
43
0
Order By: Relevance
“…Aside from motor features, there is a growing literature that demonstrates the presence of non-motor features in patients with ET [88]. Among these is cognitive impairment, which may range from mild to marked [89]. While some of this impairment likely has its basis in degenerative pathology in the cerebral cortex [90,91], some is also likely based in the cerebellum, as a cerebellar cognitive affective syndrome is well-known to occur and includes hallmark deficits in executive function [92].…”
Section: Clinicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from motor features, there is a growing literature that demonstrates the presence of non-motor features in patients with ET [88]. Among these is cognitive impairment, which may range from mild to marked [89]. While some of this impairment likely has its basis in degenerative pathology in the cerebral cortex [90,91], some is also likely based in the cerebellum, as a cerebellar cognitive affective syndrome is well-known to occur and includes hallmark deficits in executive function [92].…”
Section: Clinicalmentioning
confidence: 99%
“…While some of this impairment likely has its basis in degenerative pathology in the cerebral cortex [90,91], some is also likely based in the cerebellum, as a cerebellar cognitive affective syndrome is well-known to occur and includes hallmark deficits in executive function [92]. That executive dysfunction is a common feature of the cognitive impairment of both ET and cerebellar-related cognitive dysfunction further suggests links between ET and the cerebellum [89].…”
Section: Clinicalmentioning
confidence: 99%
“…In our study, the ETh group showed higher scores and frequency of ecmnesia than those in the ETol group. We obtained little information on the cognitive level in the patients with ETh; however, neuroimaging studies have demonstrated that the poorer cognitive performance in patients with ET might be related to gray matter atrophy or cerebellar‐cortex dysfunction, 10,26 which suggests that worse deterioration occurs in patients with ETh.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, both patient subgroups showed poor performance in the attention/memory domain; nearly half of the patients claimed to frequently forget things, which might be considered as a cognitive decline manifestation. Previous studies report 10 of increased prevalence of mild cognitive impairment and dementia in patients with ET compared with age‐matched controls 10,25 . Further, some studies have reported that besides executive dysfunction, which is the most common domain deficit in patients with ET, memory deficiency is also common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation